Survival analysis of ART restorations in primary molars of preschool children: 1 year follow-up - Marcia Falleiros Evangelista da ROCHA; Mitsue FUJIMAKI; Renata Corrêa PASCOTTO; Lucila Lemuch Castilho MENDES; Carla Martins LACERDA; Omar Cléo PEREIRA; Renata Iani WERNECK; Raquel Sano Suga TERADA
Abstract Among the minimally invasive approaches available today, the atraumatic restorative treatment (ART) has demonstrated promising results both in the primary and permanent dentition. Objective To evaluate the survival of Class I ART restorations in preschoolers with two Brazilian brands of glass ionomer cements (GIC) in comparison with a reference GIC. Material and method The cavities of 49 preschool children (three to five years) with carious lesions in the posterior teeth (N=81) were filled by two experienced pediatric dentists according to the ART technique. The Brazilian GICs Maxxion-R (MR) and Vitro-Fil LC (VF), and the reference GIC Ketac-Molar (KM) were placed in a randomly pre-established sequence. Restorations were evaluated after 6 and 12 months by another investigator. Scores 0 and 1 were considered successful, while scores 3-9 were classified as failures. Kaplan-Meier survival analysis and the log-rank test were performed (p<0.05). Result No statistically significant differences in survival rates of the tested GIC were observed after 12 months. Conclusion The clinical performance the low-cost Brazilian GICs MR and VF observed after 12 months suggests that they may be an alternative for Class I ART restorations to safeguard the natural exfoliation of primary teeth. However, until further studies involving a larger number of restorations and longer follow-up periods are conducted, reference GIC such as KM should continue to be the material of choice for ART restorations.